Advances in Hollow Inorganic Nanomedicines for Photothermal-Based Therapies - Ling C (Dove Medical Press, 2021)
Chen Ling,1 Xiaobo Wang,1 Yan Shen2 1School of Pharmacy, China Pharmaceutical University, Nanjing 211100, People’s Republic of China; 2Department of Pharmaceutics, China Pharmaceutical University, Nanjing 211100, People’s Republic of ChinaCorrespondence: Yan Shen Tel +86 (025) 83271305Email shenyan@cpu.edu.cnAbstract: Nanotechnology has prompted the development of hollow inorganic nanomedicine. These medicines are now widely investigated as photothermal-based therapies for various diseases due to their high loading capacity, tuneable wavelength, relatively small size and low density. We begin this review with a brief introduction, followed by a summary of the development of imaging-guided photothermal therapy (PTT) for cancer treatment during the last three years (from 2017 to 2020). We then introduce the antibacterial effects of these medicines on some bacterial infections, in which the pathogenic bacteria can be killed by mild photothermal effects, ions and antibiotic release. Other diseases can also be treated using hollow inorganic photothermal agents. Specifically, we discuss the use of PTT for treating Alzheimer’s disease, obesity and endometriosis. Finally, we share our perspectives on the current challenges and future prospects of using hollow inorganic materials in clinical PTT for various diseases.Keywords: hollow inorganic nanomedicine, photothermal therapy, diseases